Bioactive Fraction of Geopropolis from Melipona scutellaris Decreases Neutrophils Migration in the Inflammatory Process: Involvement of Nitric Oxide Pathway. (30th April 2013) - Franchin, Marcelo; da Cunha, Marcos Guilherme; Denny, Carina; Napimoga, Marcelo Henrique; Cunha, Thiago Mattar; Bueno-Silva, Bruno; Matias de Alencar, Severino; Ikegaki, Masaharu; Luiz Rosalen, Pedro
Abstract : The aim of this study was to evaluate the activity of the ethanolic extract of geopropolis (EEGP) from Melipona scutellaris and its fractions on the modulation of neutrophil migration in the inflammatory process, and the participation of nitric oxide (NO) pathway, as well as to check the chemical profile of the bioactive fraction. EEGP and its aqueous fraction decreased neutrophil migration in the peritoneal cavity and also the interaction of leukocytes (rolling and adhesion) with endothelial cells. The levels of chemokines CXCL1/KC and CXCL2/MIP-2 were not altered after treatment with EEGP and the aqueous fraction. It was found that the injection of NO pathway antagonists abolished the EEGP and the aqueous fraction inhibitory activity on the neutrophil migration. The expression of intercellular adhesion molecule type 1 (ICAM-1) was reduced, and nitrite levels increased after treatment with EEGP and aqueous fraction. In the carrageenan-induced paw edema model, EEGP and the aqueous fraction showed antiedema activity. No pattern of flavonoid and phenolic acid commonly found in propolis samples of Apis mellifera could be detected in the aqueous fraction samples. These data indicate that the aqueous fraction found has promising bioactive substances with anti-inflammatory activity.